2022
DOI: 10.1177/09732179211068806
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Predicts Neonatal Mortality in Eastern Africa: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Background Sub-Saharan African countries, especially the Eastern region, present the dismal picture of neonatal mortality (NM) in the globe. The majority of these deaths could be avoided if effective health measures are provided throughout pregnancy and childbirth. Although antenatal care (ANC) is assumed as one of the viable interventions that contribute to neonatal survival, the effect of ANC on NM was not systematically analyzed in Eastern Africa. Thus, the study aimed to determine the pooled effect of ANC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Mothers who had at least one ANC visit were twice as likely to vaccinate their children than those with no ANC visit. This finding is consistent with other literature indicating the importance of maternal ANC utilization in childhood vaccination [46][47][48][49]. Although four ANC visits are considered standard in Somaliland, we observed that having only one ANC visit increased the odds of their children being vaccinated compared to children of mothers who did not visit ANC at all.…”
Section: Discussionsupporting
confidence: 92%
“…Mothers who had at least one ANC visit were twice as likely to vaccinate their children than those with no ANC visit. This finding is consistent with other literature indicating the importance of maternal ANC utilization in childhood vaccination [46][47][48][49]. Although four ANC visits are considered standard in Somaliland, we observed that having only one ANC visit increased the odds of their children being vaccinated compared to children of mothers who did not visit ANC at all.…”
Section: Discussionsupporting
confidence: 92%
“…Adequate and quality ANC has been documented to contribute towards reduction of maternal and neonatal mortality. Tiruye et al showed that attending at least one ANC contact can decrease the risk of neonatal death by 42% [ 10 ]. However, SSA regions such as East Africa continue to share some of the poorest ANC utilization statistics and a significant share of global maternal and newborn mortality [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tiruye et al showed that attending at least one ANC contact can decrease the risk of neonatal death by 42% [ 10 ]. However, SSA regions such as East Africa continue to share some of the poorest ANC utilization statistics and a significant share of global maternal and newborn mortality [ 10 , 11 ]. This may be related to the quality of ANC care that is provided, which has been criticized in several studies from SSA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanism for this finding is that mothers who had ANC visits received health information from health care providers about healthy behaviors and possible medical complications during and after pregnancy, including newborn care. Also, the mothers are screened for health problems and receive curative and preventive health care services, such as tetanus immunization and iron and folic acid supplementation, to improve newborn health [ 33 ].…”
Section: Discussionmentioning
confidence: 99%